2005
DOI: 10.1177/0018726705058499
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the metaphor: The morphology of organizational decline and turnaround

Abstract: This study is based on the thesis that Vladimir Propp's (1928/2001) theory of folktale structure functions not only as a morphology of folktales, but also as a structural, deep-level model of any process that includes crisis and recovery. We essentially suggest that corporate decline and turnaround processes can be emplotted into a folktale-like structure that supports Propp's theory and thereby helps uncover deep-level mechanisms governing the process. The developed model describes seven mechanisms that drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…For example, access to crucial power bestowing resources can help organizations survive during periods of crisis (Lamburg and Pajunen, 2005). Finally, a study of human service organizations in the US found that firms with many linkages with the environment were able to control the coercive power wielded by larger organizations they depend upon for resources (Provan et al, 1980).…”
Section: Coercion 'Through' Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, access to crucial power bestowing resources can help organizations survive during periods of crisis (Lamburg and Pajunen, 2005). Finally, a study of human service organizations in the US found that firms with many linkages with the environment were able to control the coercive power wielded by larger organizations they depend upon for resources (Provan et al, 1980).…”
Section: Coercion 'Through' Organizationsmentioning
confidence: 99%
“…Formal Authority (Weber, 1947) Bases of power (French and Raven, 1959) Control of sources of uncertainty (Crozier, 1964) Control over valuable resources (Pfeffer and Salanick, 1974) CEO control over scarce resources (Hambrick, 1981) Control over resources need by stakeholders (Elg and Johansson, 1997) Organization use of resources to fend off unwanted environmental pressure (Lamburg & Pajunen, 2005) Social movements mobilize valuable resources to pressure change in firms (McCarthy & Zald, 1997) Undermining existing resource flows (Hiatt et al, 2009) …”
Section: Coercionmentioning
confidence: 99%
“…Formalization is not only associated with exploitation (March, 1991), but is also conducive to exploration (Farjoun, 2010) because it stimulates knowledge sharing (Baum and Wally, 2003) and provides guidance for non-routine activities (Dougherty, 2006). In a turnaround context, formalization fosters retrenchment by ensuring tighter resource control (Hoffman, 1989), but it can also help define expectations and ensure organizational commitment to recovery objectives (Lamberg and Pajunen, 2005;Simons, 1994). Conversely, participative settings not only enable exploration (Kang and Snell, 2009), but ensure employees' cooperation and mutual trust in exploitation activities (Adler et al, 2009).…”
Section: An Alternative View: Retrenchment and Recovery As A Dualitymentioning
confidence: 99%
“…Scholars explore two essential categories of turnaround activities: retrenchment and recovery (Robbins and Pearce, 1992;Sudarsanam and Lai, 2001). While retrenchment focuses on increasing efficiency through cost and asset reductions, recovery concentrates on improving a firm's market position through strategic change (Lamberg and Pajunen, 2005). Since prior research describes retrenchment and recovery as contradictory forces (Pearce and Robbins, 2008), scholars generally advise turnaround firms to opt for one or the other (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to the study of turnaround identifies the actions taken by managers of turnaround businesses which reverse firm-threatening performance declines [1,2,3]. Another group of studies examines organizational responsiveness to change including crisis and decline [4,5,6]. The third group of studying corporate turnaround has involved identifying the changes in corporate financial characteristics and /or environmental contexts that associated with turnaround [7,8,9].…”
Section: Introductionmentioning
confidence: 99%